Awareness and self-awareness in the teaching / learning of language-culture: why? what? how? - Smuk, Maciej (Glottodidactica, 2022)
The article introduces different approaches to (self-)awareness, as presented in this issue of Glottodidactica. Its first part discusses the advantages of developing (self-)awareness – in relation to the foreign language teacher and the foreign language learner. The general concept of savoir-être competence (existential competence) is also mentioned. In the second part possible research perspectives in this area and examples of research are given. The third part lists techniques and tools which can be used to stimulate teacher and student self-awareness.